Pengembangan Biolarvasida Jentik Nyamuk Aedes aegypti Berbahan Aktif Ekstrak Beluntas (Pluchea indica Less.) - Agus Rochmat; Mitha Fuji Adiati; Zahrotul Bahiyah (Reaktor, 2016)
Abstract POTENSIAL DEVELOPMENT OF EXTRACT BELUNTAS (Plucea indica Less.) as BIOLARVACIDE TO MOSQUITO Aedes aegypti LARVAE. The eradication of Aedes aegyptY mosquito is difficult because they have the ability to adapt the environment which makes it very tough. Although, there are not disturbances due to natural phenomena or human intervention. Termination of the mosquito life cycle is an alternative to reduce the mosquito population. The antimicrobial of beluntas extract is expected to have the ability biolarvacide on mosquito larvae. The biolarvasicide of beluntas leaf extracts was determined LC50 values and strengthened by identification of the active compound. The biolarvacide tested was conducted on the larvae of Aedes aegypti with variations extract concentrations of 50, 100, 250, 500 and 1000 ppm for 24 hours observation. The experimental results found that yield of ethanol extract, extract n-hexane and ethyl acetate extract: 3.8742%, 1.2054% and 1.8627%. While the value of LC50 to extract n-hexane and ethyl acetate respectively amount to 46.09 ppm and 108.79 ppm. LC50 value obtained belong biolarvacide active and positive control using abate value LC100 Abate at a concentration of 100 ppm. The ability biolarvacide ethyl acetate fraction only make the mosquito larvae die, anwhile the fraction of n-hexane can degrade the cells larvae destroyed. The ability biolarvacide beluntas extract was corroborated by the results of GC-MS analysis which showed contains active compounds beluntas such as quinic acid, hydrazinecarboxamide, benzene acetic acid, and 1,2-benzendicarboxylic acid which is a compound of larvicides. Keywords: biolarvacide; beluntas; LC50, GC-MS  Abstrak Pemberantasan nyamuk Aedes aegypti sulit dilakukan karena mereka memiliki kemampuan adaptasi lingkungan yang membuat sangat tangguh, meski ada gangguan  akibat  fenomena  alam ataupun  intervensi manusia. Pemutusan siklus hidup nyamuk merupakan alternative dalam mengurangi populasi nyamuk. Sifat antimikroba ekstrak nyamuk diharapkan dapat memiliki kemampuan biolarvasida pada jentik nyamuk. Kemampuan biolarvasida ekstrak daun beluntas ditentukan melalui nilai LC50 dan diperkuat dengan identifikasi kandungan senyawa aktif. Uji biolarvasida ini dilakukan terhadap larva nyamuk Aedes aegypti dengan variasi konsentrasi ekstrak 50, 100, 250, 500 dan 1000 ppm selama 24 jam pengamatan. Hasil percobaan diketahui bahwa: rendemen untuk ekstrak etanol, ekstrak n-heksana dan ekstrak etil asetat masing-masing sebesar 3,8742 %, 1,2054 % dan 1,8627 % sementara nilai LC50 untuk ekstrak n-heksan dan etil asetat masing-masing sebesar 46,09 ppm dan 108,79 ppm. Nilai LC50 yang diperoleh termasuk golongan biolarvasida aktif dan kontrol positif menggunakan abate memiliki nilai LC100 Abate pada konsentrasi 100 ppm. Kemampuan biolarvasida fraksi etil asetat hanya membuat larva nyamuk mati sementara fraksi n-heksana dapat mendegradasi sel larva hingga hancur. Kemampuan biolarvasida aktif ekstrak beluntas ini dikuatkan dengan hasil analisa GC-MS yang menunjukkan bahwa kandungan senyawa aktif ekstrak daun beluntas seperti quinic acid, hydrazinecarboxamide, benzene acetic acid, dan 1,2-benzendicarboxylic acid yang merupakan senyawa larvasida.